Dynamics of net ecosystem methane exchanges on temporal scale in tropical lowland rice. (October 2018) - Swain, C.K.; Bhattacharyya, P.; Nayak, A.K.; Singh, N.R.; Neogi, S.; Chatterjee, D.; Pathak, H.
Abstract: Net ecosystem methane exchanges (NEME) from lowland rice often show significant variations in diurnal, seasonal and yearly scales and with crop phenology. Air and soil temperatures, standing water, and radiation are believed to be primary drivers of such variations. We studied the dynamics of net ecosystem methane exchange in three consecutive years (2014–16) using eddy covariance technology. Wet season (July–October) showed higher diurnal methane flux variations than that of dry season (December–March) due to prolonged anoxic condition and higher methanogens in the former. Significant diurnal variations in NEME were also noticed during different crop growth stages. Variations were higher in flowering stage followed by ripening in 2015 and 2016. But in 2014, it was highest at panicle initiation (PI) stage. Principal component bivariate plot analysis and performance analytic correlation were performed for variables such as net ecosystem carbon dioxide exchange (NEE), NEME, sensible heat (Hs), latent heat (LE), photosynthetically active radiation (PAR), net radiation (NR), air temperature and soil temperature (5 cm depth) in order to assess their relationships. The NEME was positively correlated to air and soil temperatures in all the years. However, in year 2016, NEME also showed positive correlation to PAR and NR. These relationships could provide valuable information to partitioning and process-based simulation modelling for projecting and up scaling of NEME to regional and global scales. Graphical abstract: Image 1 Highlights: Significant diurnal, seasonal and yearly variations noticed in NEME lowland rice. Wet season NEMEs were higher than that of dry seasons. NEME was positively correlated to air, soil temperatures and LE. NEMEs were higher in flowering stage followed by ripening.